Long-term outcome after the original and simple modified technique of valve-sparing aortic root reimplantation in Marfan-based population, David V University of Tokyo modification. Issue 1 (January 2016) - Ando, Masahiko; Yamauchi, Haruo; Morota, Tetsuro; Taketani, Tsuyoshi; Shimada, Shogo; Nawata, Kan; Umeki, Akihide; Ono, Minoru
Abstract: Background: In valve-sparing aortic root replacement (VSARR), how to reproduce Valsalva sinus has been an issue. In the original David V procedure, they put plication stitches at sinotubular junction level, although the reefing effect is limited and distal graft remains larger than native. Other modified techniques are two-grafts technique and ready-made Valsalva graft. However, the former needs graft–graft anastomosis and may not be cost-effective, while in the latter, the shape of sinus is fixed and minor adjustment is difficult. David V University of Tokyo modification (David V-UT) is our original solution to that, creating pseudosinus with one straight graft by longitudinal size-reduction running sutures above each pseudosinus. The purpose of the present study is to investigate long-term outcome of David V-UT. Methods: We analyzed 59 David V-UT patients from February 2004 to February 2013 and long-term outcomes were investigated by Kaplan–Meier methods. Risk factors for adverse events "death or recurrent aortic insufficiency (AI) with or without aortic valve reoperation" were analyzed by using Cox proportional hazard models. Results: Mean age was 33.1 ± 14.5 years, and 38 patients (64%) were male. Marfan syndrome (MFS) accounts for 47 patients (80%). Only one patient was with bicuspid aortic valve. No in-hospital mortality was observed. Mean follow-up was 4.9 ± 2.4 years. Estimated survival was 94.0 ± 3.4% at 5 years. Freedoms from aortic valve reoperation and recurrent AI greater than mild were 95.7 ± 3.0% and 88.9 ± 4.7% at 5 years, respectively. In Cox proportional hazard analysis, preoperative AI greater than mild and Z score of annular diameter were significant risks for adverse events ( p  = 0.027 and 0.045, hazard ratio 6.084 and 1.432, 95% C.I. 1.225–30.21 and 1.008–2.035, respectively). Conclusions: Even in Marfan-characterized population, David V-UT provided satisfactory long-term outcome, comparable to other VSARR modifications. It is simple but can freely reproduce trilobed sinus with one straight graft.